Influence of polymorphic loci rs1800629 (TNFa), rs6074022 (CD40), rs187238 (IL-18), rs10492972 (KIF1B), rs4149584 (TNFRSF1A) on clinical features of multiple sclerosis subject to sex belonging in Russian ethnic group - Ye. V. Khanokh; A. S. Rozhdestvensky; Ye. A. Kudryavtseva; A. V. Kakulya; R. A. Delov; M. A. Filipenko (Бюллетень сибирской медицины)
To study influence of polymorphic loci rs1800629 (TNFa), rs6074022 (CD40), rs187238 (IL-18), rs10492972 (KIF1B), rs4149584 (TNFRSF1A) on clinical features of multiple sclerosis (MS) subject to sex belonging in Omsk city and Omsk region. Methods: neurological examination, molecular-genetic, statistic analyses. 265 patients with multiple sclerosis and 576 healthy controls was observed. Results: observable polymorphic loci don’t associated with sex. In group of men dysfunction of the pyramidal, visual, pelvic functions on course of MS, in women group — dysfunction of the pyramidal functions, duration of the disease, height, CD40 genotipe.